The Importance of Investing in the Human Capital A reviewing of The Malaysian Experience and The possibility of Being Benefit - محلا رباب (Latakia University Journal - Economic and Legal Sciences Series, 2025)
Since the beginning of the new millennium, it has become more and more apparent that education and human capital constitute a key element in enhancing economic growth and creating economic development., and a means of transitioning into a knowledge economy that based on creativity and innovation. This makes so necessity, to understand the concepts of human capital investment, and the importance of the success of educational policies, especially the developing and utilizing human capital skills and knowledge extends beyond the current workforce to the potential workforce as well. Accordingly, the research aims to exploring the development of human capital investment concept, and all related theoretical issues, as one of economic life factors, and reviewing the Malaysian experience, which is considered a pioneering and unique experience in this context, in addition. Importance of the Research: The importance of the research is linked to the role of investment in human capital as one of the most crucial factors for achieving desired economic growth rates. It serves as a fundamental pillar in establishing the sought-after economic development and a means of transition from an economy based on traditional production processes to a knowledge economy driven by skills, creativity, and innovation, keeping pace with the rapid technological advancements witnessed globally. Results: The emergence and development of the concept of human capital are associated with the evolution of economic studies that have focused on economic growth and the factors influencing it. In this regard, Theodore Schultz clarified that although it is known that individuals acquire useful skills and knowledge, it was not recognized that these skills and knowledge represent a form of capital, and that this form of capital is, to a significant extent, essential.